Адсорбція катіонів Pb2+ з плазми крові нанокомпозитами на основі магнетиту - Kusyak, A. P.; Petranovska, A. L.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
The adsorption capacity of magnetite and Fe3O4/SiO2, Fe3O4/TiO2 и Fe3O4/Al2O3 composites towards Pb2+ cations in human serum was investigated. The effect of the solvent and the stabilizer on the adsorption of lead cations and protein compounds in blood serum medium was studied. The effect of chemical modification of the magnetite surface on adsorption properties of the synthesized composites was showed. The conclusion about prospects of synthesized nanocomposites as a medical-biological sorbents, its technical and environmental purposes was made.